Early successful weaning from continuous positive airway pressure in infants <32 weeks of gestation: predictors of success - Bünte, Lisa Marie; Walden, Christina; Schlecht, Jennifer; Bubl, Benedikt; Popa-Todirenchi, Mircea-Horia; Tippmann, Susanne; Winter, Julia; Mildenberger, Eva; Kidszun, André (Frontiers in Pediatrics, 2025)
AimTo identify demographic and clinical variables predictive of early successful weaning in preterm infants weaned off continuous positive airway pressure (CPAP).MethodsSingle-center retrospective analysis of preterm infants < 32 0/7 weeks gestational age (GA) weaned off CPAP according to a standardized protocol April 2013–March 2017. Infants were categorized into (1) early successfully weaned (Early-W) if weaned at the first attempt and (2) delayed weaned (Delayed-W) if more than one attempt was necessary. Potential predictor variables were predefined. Association with Early-W was analyzed by multivariable logistic regression with model selection using the Akaike information criterion (AIC). Model performance was evaluated using the area under the receiver operating characteristic (ROC-AUC).Results145 infants [79 (54.5%) were Early-W and 66 (45.5%) Delayed-W] with complete data sets were included in the analysis. A model of higher GA [odds ratio (OR) 1.66; 95% confidence interval (CI) 1.39, 2.03; p < 0.001], present patent ductus arteriosus (PDA) (OR 0.41, 95% CI 0.16, 1.04; p = 0.062) and higher median respiratory rate (RR) in the previous 12 h (OR 0.36; 95% CI 0.16, 0.74; p = 0.008) best predicted Early-W (ROC-AUC: 0.841).ConclusionThis study identified GA, PDA and median RR to predict early successful weaning in preterm infants weaned off CPAP. The predictive value of median RR in the 12 h prior to CPAP cessation is considered a novelty requiring further prospective investigation, with RR being a clinical parameter commonly employed in routine practice and practical for everyday application.